1988
DOI: 10.1159/000242856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition on Postnatal Development of Serine-Threonine Dehydratase and Branched-Chain Keto Acid Dehydrogenase in the Rat

Abstract: The developmental patterns of two amino acid-catabolizing enzymes, serine-threonine dehydratase (STD) and branched-chain α-keto acid dehydrogenase (BCKAD), were investigated in growing rats. At 10, 15, 20, 30, and 60 days of age, STD and BCKAD activities were determined in pup tissues. Hepatic STD activity increased more than 3-fold between 10 and 20 days of age; after this peak, activity decreased by 30 days of age. Threonine dosing did not affect STD activity at any age. In the liver, kidney, brain and skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…Similar results on heart actual and total activities were described by Veerkamp et al [10]. Grogan et al [11] reported similar results for the skeletal muscle and brain for 10-day-old to 30-day-old suckling rats. The proportion of the heart enzyme that was dephosphorylated and active was greater during the suckling period than observed with the heart enzyme of mature animals [12,19].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results on heart actual and total activities were described by Veerkamp et al [10]. Grogan et al [11] reported similar results for the skeletal muscle and brain for 10-day-old to 30-day-old suckling rats. The proportion of the heart enzyme that was dephosphorylated and active was greater during the suckling period than observed with the heart enzyme of mature animals [12,19].…”
Section: Discussionsupporting
confidence: 84%
“…An age-dependent increase in BCODC activity during neonatal development of the rat has been documented previously by others [9][10][11]. The work of May et al [9] first described the developmental pattern for the liver, but whether the increase throughout the suckling period was due to a change in enzyme mass or covalent modification was not investigated.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It has been reported [46] that the liver BCKDC activity increases in rat pups throughout the suckling period, reaching adult levels at the age of weaning (21 days). In addition, total BCKDC activity in the liver rises during postnatal development (until 30-40 days of age) and then tends to drop at around 60 to 70 days of age [47,48]. To our knowledge, no further information is available regarding age-dependent changes in rat hepatic BCKDC activity after 10 weeks of age; thus, this issue needs further clarification in future studies.…”
Section: Discussionmentioning
confidence: 91%